2010
DOI: 10.1002/marc.201000237
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Optically Active Polymer with P‐Stereogenic Phosphine Units

Abstract: Optically active polymer containing P-stereogenic bisphosphine as a repeating unit in the main was successfully synthesized. A coordinated borane on the phosphorus atom could be completely removed by an organic base under mild condition, and the successive reaction with Pd afforded the corresponding polymer complex. The chirality of P-stereogenic centers was transferred to the m-phenylene-ethynylene linkers by complexation because of the prohibition of the rotary motion of the bisphosphine-Pd unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…reported the synthesis of 3 by reacting 3,5‐dibromophenol with 1‐bromododecane in the presence of K 2 CO 3 (as base) and dimethyl ketone as solvent. The reaction mixture was refluxed for 18 h and the yield of the reaction was 84% . We observed that if 3,5‐dibromophenol and K 2 CO 3 are allowed to stir in DMF for 1 h followed by dropwise addition of n ‐dodecyl bromide and stirring the reaction mixture at 75 °C, the formation of the desired 3 is almost quantitative in 2 h (Scheme ).…”
Section: Resultsmentioning
confidence: 95%
“…reported the synthesis of 3 by reacting 3,5‐dibromophenol with 1‐bromododecane in the presence of K 2 CO 3 (as base) and dimethyl ketone as solvent. The reaction mixture was refluxed for 18 h and the yield of the reaction was 84% . We observed that if 3,5‐dibromophenol and K 2 CO 3 are allowed to stir in DMF for 1 h followed by dropwise addition of n ‐dodecyl bromide and stirring the reaction mixture at 75 °C, the formation of the desired 3 is almost quantitative in 2 h (Scheme ).…”
Section: Resultsmentioning
confidence: 95%
“…We attempted to remove the boranes coordinated with the phosphorus atoms in tetraphosphine (S,R,R,S)-8 ÀBH 3 by using organic bases such as morpholine 23 [11][12][13] ). When (S,R,R,S)-8 ÀBH 3 was stirred in morpholine for 48 h, all the boranes were readily removed.…”
Section: P-stereogenic Oligophosphinesmentioning
confidence: 99%
“…[2][3][4][5][6] However, despite the widespread use of P-stereogenic phosphines, polymers containing chiral phosphorus atoms in their backbones have rarely been prepared. 7 Recently, we synthesized P-stereogenic optically active polymers [8][9][10][11][12][13] and oligomers [14][15][16] using P-stereogenic bisphosphines as chiral building blocks. These molecules formed higher-ordered chiral structures derived from P-stereogenic centers, and their conformations could be controlled through metal coordination with bisphosphine moieties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have focused on P‐stereogenic bisphosphines ( S,S )‐ 1 –BH 3 and ( S,S )‐ 2 –BH 3 , which were reported by Evans28 and Imamoto,29 respectively, as building blocks for optically active cyclic compounds,30–32 oligomers,33–35 dendrimers,36 and polymers 37–41. The incorporation of the P‐stereogenic bisphosphines into the polymer main chain leads to the construction of optically active polymers.…”
Section: Introductionmentioning
confidence: 99%